Futuros en contrapunto: proyección, predicción y deseo en maya yucateco - Valentina Vapnarsky (Journal de la Société des Américanistes)
This paper studies the ways in which the contemporary Yucatec Maya apprehend the future and project themselves into it. It is based on an analysis of linguistic choices in the expression of prospective utterances, which are examined ethnographically in the midst of communicative situations. Yucatec Maya distinguishes between two major perspectives of the future: a future of predetermined events beyond the control of human action, which are known but are disconnected from present action (bíin), and a future in continuity with the potentialities of the speech event and the contemporary world, expressed by a broad range of other prospective forms: imminent and ingressive mika’aj, deontic and projective yan, desiderative tak, assertive je’el, etc. Through a situated analysis of the use of these prospective forms, this paper attempts to elucidate how Maya interlocutors, in more or less ordinary everyday activities and circumstances, contrast forms of instigation and control, engagement and disengagement, as well as necessary or intentional causality. The ultimate aim is to reveal Maya typified stances in relation to the future, and show how these connect with temporal, intersubjective, epistemic and agentive frames.